Le programme d’enseignement général à l’université de Stanford de 1935 à 1998 : transmission de substances de référence ou construction de métasubstances ? - Agnès Bouchet-Sala (Revue LISA)
General Education frequently involves studying several disciplines, and aims to provide a common culture and experience for all students entering a particular institution. As cultural constructs, emblematic of American society’s self representation at a given time, the cultural contents of these courses are not neutral. The recent debates over the “sacrality” of the reading list (the “canon of Great Works”) bear testimony to the interests at stake. Yet, the purpose of such courses could be less to furnish the mind with some reference substance than to enable students to build a cross-cultural understanding of the various human experiences, or metasubstance. Therefore, it not only questions the choice of the cultural contents, but also the nature of the substance to be transmitted, or in other words, the initial ambition of the General Education Course.